The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/1516-3180.2020.0412.r1.28012021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bundle implementation on the incidence of peri/intraventricular hemorrhage among preterm infants: a pre-post interventional study

Abstract: BACKGROUND: Peri/intraventricular hemorrhage (PIVH) is a frequent cause of death and morbidity among preterm infants. Few studies have addressed the use of bundles for preventing PIVH. OBJECTIVE: To evaluate the efficacy of a bundle of interventions designed to decrease the incidence of intraventricular hemorrhage at hospital discharge among preterm infants. DESIGN AND SETTING: Pre-post interventional study with retrospective and prospective data collection performed before and after bundle implementation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A review of studies published in 2021 not included in our meta-analysis reported a wide range of incidences and GA inclusion criteria, demonstrating the significant heterogeneity in the literature: any IVH 13%–40% for GA 28–29 weeks,23 24 27% for GA <30 weeks,25 25%–29% for GA <32 weeks,23 12% for GA <34 weeks26 and 2% for GA 34–35 weeks;27 sIVH 29% for GA 22–24 weeks and 9% for GA 25–28 weeks,28 15%–29% for GA <32 weeks29 30 and 4% for GA <34 weeks 26. A systematic literature review of global incidence of sIVH between 2006 and 2017 ranged from 5% to 52% (our 95% CI for this age group was 13% to 17%) with the majority of studies reporting incidence <20% 7…”
Section: Discussionmentioning
confidence: 95%
“…A review of studies published in 2021 not included in our meta-analysis reported a wide range of incidences and GA inclusion criteria, demonstrating the significant heterogeneity in the literature: any IVH 13%–40% for GA 28–29 weeks,23 24 27% for GA <30 weeks,25 25%–29% for GA <32 weeks,23 12% for GA <34 weeks26 and 2% for GA 34–35 weeks;27 sIVH 29% for GA 22–24 weeks and 9% for GA 25–28 weeks,28 15%–29% for GA <32 weeks29 30 and 4% for GA <34 weeks 26. A systematic literature review of global incidence of sIVH between 2006 and 2017 ranged from 5% to 52% (our 95% CI for this age group was 13% to 17%) with the majority of studies reporting incidence <20% 7…”
Section: Discussionmentioning
confidence: 95%
“…Because of this and the high interest in child health evidenced by national strategies has led to an increased investment and development in neonatal care so as to improve survival rates [10]. The resulting high number of preterm, very low birth weight (VLBW) and extremely low birth weight (ELBW) newborns increases the risk of intracranial bleeding occurring, and intraventricular haemorrhage (IVH) in particular; with neonates born <32 weeks gestation age (GA) or <1500g being more susceptible [11,12]. While IVH contributes significantly to poor outcomes in mortality, morbidity, cognitive and motor neurological development, there is little data in its incidence, risk factors and complications in LICs as compared to high income countries [12].…”
Section: Introductionmentioning
confidence: 99%